Stress and Coping Strategies among Students: Review - J.A. Marakshina; V.I. Ismatullina; L.M. Marina (Клиническая и специальная психология)
Global socio-economic crises, new pandemics, climate disasters, and other large-scale factors create an unfavorable background for humanity, often involving painful processes that lead to significant changes in personality and the social situation of development. Students, as they navigate personal and professional development during their university education, determine their life prospects and societal roles for many years to come. A normative age crisis, combined with everyday and global stresses, can lead to adverse consequences such as high anxiety, depression, post-traumatic stress disorders, other emotional and behavioral problems, and social maladjustment. The issue of coping strategies that help students effectively manage stress becomes increasingly relevant. The review included 75 full-text Russian and English papers, mainly from 2019–2024, sourced from bibliographic databases such as Elibrary, Google Scholar, and PubMed. The analysis included articles where the participants were aged 17–25, primarily students. The analysis of theoretical and empirical studies allowed us to systematize the types of students' stressors and the specifics of coping strategies. It is important to distinguish whether coping is a response to a specific stressor (situational coping) or if its use is related to an individual's personality traits (dispositional coping). Additionally, it is informative to consider socio-demographic characteristics such as the gender of participants, year, and field of education, which help to identify additional factors associated with the use of different coping strategies. The choice of effective or ineffective coping strategies is characterized by different relationships between stress, existing emotional problems (such as anxiety and depression), and mental toughness (adaptive resource). Thus, a scientifically based approach to effective coping strategies for students, with detailed consideration of perceived stress, mental toughness, the level of emotional problems, and demographic factors, can be considered the most relevant theoretical model.